2013
DOI: 10.1177/0748233713504807
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of onion (Allium cepa) extract against doxorubicin-induced hepatotoxicity in rats

Abstract: Our study indicates that pretreatment with ACE protects against DOX-induced hepatotoxicity due to the antioxidant properties of ACE. Further studies on efficacy of antioxidant treatment by ACE in DOX-mediated toxicity and underlying mechanisms would provide a better explanation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 28 publications
(28 reference statements)
3
11
0
Order By: Relevance
“…Also, DOX caused high percentage of structural and numerical chromosome aberrations. These results are similar to the previous studies which provided evidence that DOX induced hepatotoxicity and chromosomal aberrations [29][30][31]. On the other hand, Herbs are rich in various compounds such triglycerides, flavonoids, and polyphenols, that can defend against damages induced by toxic drugs [32].…”
Section: Discussionsupporting
confidence: 81%
“…Also, DOX caused high percentage of structural and numerical chromosome aberrations. These results are similar to the previous studies which provided evidence that DOX induced hepatotoxicity and chromosomal aberrations [29][30][31]. On the other hand, Herbs are rich in various compounds such triglycerides, flavonoids, and polyphenols, that can defend against damages induced by toxic drugs [32].…”
Section: Discussionsupporting
confidence: 81%
“…A recent study stated that DOX-treated group can increase both ALT and AST enzymes activity because of the liver damage and it is confirmed by the histological results (Barakat et al, 2018). The present results showed that DOX-treated group sections which stained with H&E showed focal hepatocyte necrosis and the hepatotoxicity that resulted are in accordance with Jambhulkar et al, (2014) and Mete et al, (2016) results which stated a parenchymal necrosis and proliferation of biliary ducts in DOXtreated group. Vacuolation of hepatocytes was reported as one of cellular defensive mechanism as they can collect the harmful elements and prevent their interfering with the biological functions of these cells and Pyknosis and karyolysis of the nuclei may be attributed to the loss of functional efficiency (AL-Mosaibih, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Alpsoy et al ., recently showed that onion extracts have a protective effect on cadmium-induced oxidative stress [ 38 ]. Similarly, Mete et al ., reported that pretreatment with onion extract protects against doxorubicin-induced hepatotoxicity due to its antioxidant properties [ 39 ]. In addition, previous studies have shown that flavonoids afford cyto-protective effects against micronucleus induction in irradiated mice and lymphocytes [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%